2021
DOI: 10.3390/ijms22094387
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib as a Valuable Adjuvant in Cutaneous Melanoma Treated with Trametinib

Abstract: Background: Melanoma patients stop responding to targeted therapies mainly due to mitogen activated protein kinase (MAPK) pathway re-activation, phosphoinositide 3 kinase/the mechanistic target of rapamycin (PI3K/mTOR) pathway activation or stromal cell influence. The future of melanoma treatment lies in combinational approaches. To address this, our in vitro study evaluated if lower concentrations of Celecoxib (IC50 in nM range) could still preserve the chemopreventive effect on melanoma cells treated with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Starting from viability tests we observed that melanoma cells manifested sustained resistance to usual doses of dabrafenib (1–100 nM—data not shown), therefore, we had to increase dabrafenib doses in order to achieve IC 50 (200–700 nM) [ 30 ]. Similar to our previous expertise, celecoxib did not alter cell viability as a single compound [ 14 ]. However, the celecoxib and dabrafenib combination induced a time and dose-dependent cytotoxic effect in both A375 and SK-MEL-28 cell lines.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Starting from viability tests we observed that melanoma cells manifested sustained resistance to usual doses of dabrafenib (1–100 nM—data not shown), therefore, we had to increase dabrafenib doses in order to achieve IC 50 (200–700 nM) [ 30 ]. Similar to our previous expertise, celecoxib did not alter cell viability as a single compound [ 14 ]. However, the celecoxib and dabrafenib combination induced a time and dose-dependent cytotoxic effect in both A375 and SK-MEL-28 cell lines.…”
Section: Discussionsupporting
confidence: 85%
“…Among them, phenotype switching, represented by a low MITF/AXL ratio, has gained a lot of attention [ 24 ]. In a previous work, we showed that low-dose celecoxib exerts antineoplastic effects in a melanoma co-culture treated with trametinib, by decreasing phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) resistance pathway activation [ 14 ]. Moreover, what is already known about the antineoplastic capabilities of celecoxib in melanoma, independent from COX-2/prostaglandin E2 (PgE 2 ) inhibition, is that it suppresses cancer cell growth and promotes apoptosis via Wnt/β-catenin and m-TOR (mechanistic target of rapamycin) substitutive pathway inhibition, and reduces the epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), and the signal transducer and activator of transcription 3 (STAT3) expression [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different findings pointed out that GS seems to exert its effect on NF-κB-dependent transcription via an epigenetic mechanism, regulating the demethylation of specific CpG sites of DNA in the IL1β promoter, responsible for the aberrant expression of MMPs, ADAMTS, and IL-1β in human articular chondrocytes [37,54]. On the other hand, it is currently not completely defined how celecoxib mediates the activity of NF-κB, but it is possible to assume that it follows the PI3K/AKT/IKK/NF-kB pathway regulation, implicated in the regulation of apoptosis and cell proliferation, as demonstrated in different studies on cancer cell lines [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical ones revealed that, implication of celecoxib resulted in reduction of implanted cancer cell growth, decrease in angiogenesis, and fighting of metastases. 8 The clinical trials conducted recently to evaluate the role of celecoxib in enhancing the effect of chemotherapy showed either modest effect or lack of effect. 9 - 11 Thus, additional clinical trials on the anti-tumor efficacy of celecoxib are still required to provide results oriented clinical data.…”
mentioning
confidence: 99%